The role of soil, water and forest conservation on vegetation cover and landscape greenness in degraded areas of upper Blue Nile - Mengie Belayneh; Teshome Yirgu; Dereje Tsegaye (Brawijaya University, 2021)
Recently, large-scale soil, water, and forest conservation/protection practices have been implemented in Ethiopia. This study aimed to evaluate the impact of soil, water, and forest conservation/protection on vegetation cover and landscape greenness in the Gumara watershed. Landsat satellite imageries were used to analyze the changes using land use/cover and net difference vegetation index (NDVI) and its differencing methods. Over the period 1995-2017, forestland and shrub-woodland covers increased by 48.4% (2.8-4.2%) and 8.3% (20.2-21.9%), respectively. Similarly, the NDVI result showed high improvements in landscape greenness and vegetation density. A 13.5% of the watershed area experienced a significant increase, of which 61.4% was observed on forest and shrub-woodland covers. The watershed area covered by very high (NDVI>0.4) and high (NDVI 0.3-0.4) vegetation density classes were increased by 189.2 and 145.5%, respectively. Upon the increasing human pressure and related problems, the observed improvement of vegetation cover and landscape greenness show the positive impact of soil, water, and forest conservation/protection practices done for the last two decades. Therefore, strengthening the current efforts and investing more in sustainable and evidence/priority-based soil, water, and forest conservation measures that are ecologically friendly with diversified livelihood importance can bring a more effective result of land rehabilitation.